Assessment of river water quality in Kathmandu valley: A physico-chemical and microbial analysis - Arjyal, Charu; Maharjan, Jasna; Budhathoki, Akriti; Panthi, Girija; Khadka, Karuna; Regmi, Pragya (Scientific World, 2025)
Water pollution is emerging as a serious environmental issue, challenging public health and ecological integrity. The present study was carried out to evaluate the physico-chemical and microbiological parameters of the Bagmati River and some of its tributaries (Dhobikhola, Manohara and Tukucha rivers) following American Public Health Association (APHA) standard methods. The Most Probable Number (MPN) method was used for the enumeration of coliforms. Furthermore, Water Quality Index (WQI) was calculated for the river water samples to determine if the quality of water is suitable for human consumption. Altogether 24 water samples were collected from 4 different sampling sites from December 2023 to February 2024. The pH of the water samples was observed to be slightly basic in nature (6.5 to 8.16). The physico-chemical parameters such as temperature, pH, Total Hardness (TH), and Chloride (Cl-) were within the limits prescribed by National Drinking Water Quality Standard (NDWQS) of Nepal. The dissolved oxygen (DO) values, alkalinity and Biological oxygen demand (BOD) in the river water samples were variable, i.e. (1.02 - 3.50) mg/L, (130 – 235) mg/L, and (76.8 – 285) mg/L, respectively. The coliform count ranged between 210 - 2400 cfu/100 mL, was above NDWQS threshold limit indicating high microbial load in river water. The bacterial species isolated were Escherichia coli (79%), Salmonella (67%), Enterobacter (42%), Citrobacter (42%), Klebsiella (33%). The presence of thermotolerant E. coli in 45.83 % of the samples indicated the recent contamination of the river water with fecal matter. Antibiotic susceptibility test by Kirby Bauer disc diffusion method showed that all the bacterial isolates were resistant to Ampicillin. Similarly, the observed WQI values of river water samples were found to be in a range (13.52 - 37.52). Though, WQI values were low, the river water samples exhibited very low DO values, high alkalinity and high BOD values as well as high microbial load which indicated Bagmati river and its tributaries are highly polluted and unsafe for consumption without further treatment.